A new strategy for the synthesis of 2-mercaptobenzazole derivatives by green chemistry metrics. (2nd January 2021) - Vessally, Esmail; Monfared, Aazam; Eskandari, Zahra; Abdoli, Morteza; Hosseinian, Akram
Abstract: A green and efficient method has been developed for the synthesis of 2-mercaptobenzazole derivatives via the reaction of commercially available aniline derivatives with low-cost and nontoxic potassium thiocyanate in water. The reactions proceeded smoothly under catalyst- and ligand-free conditions to give the corresponding products in good to excellent yields. The versatility, low cost, and environmental friendliness, in combination with high yields and easy work-up makes the procedure noteworthy. Graphical Abstract: